The associations between circulating amino acids and arterial aneurysms and dissection: A bidirectional Mendelian randomization study - Xiaodong Li; Yarong Ma; Qiulin Jiang; Huizhi Zhan; Xiaolei Sun (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Circulating amino acid levels can be altered in arterial aneurysms and dissection, but the relationships between them is unclear. The present study investigated the causal relationship between circulating amino acid levels and arterial aneurysms and dissection via bidirectional two-sample Mendelian randomization (MR). Methods: A bidirectional two-sample MR analysis was used. Forward analysis was performed with amino acid levels as the exposure and arterial aneurysms and dissection as outcomes. Reverse analysis was performed with arterial aneurysms and dissection as exposures and circulating amino acid levels as outcomes. MR data were analyzed using five analytical methods: the inverse-variance weighted (IVW), MR‒Egger, weighted median, simple, and weighted methods. IVW was used as the main analytical method, and the other methods were used for supplementary analyses. Heterogeneity was assessed using Cochran's Q test, and horizontal pleiotropy was assessed using intercepts from MR‒Egger regression. The genome-wide association study (GWAS) data for circulating amino acids were obtained from the IEU open GWAS database and the GWAS Catalog database. The GWAS data for arterial aneurysms and dissection were obtained from the Finngen consortium database version R10. Results: The tyrosine level was negatively correlated with other aneurysms (P = 0.00211, OR: 0.57, 95 % CI: 0.40, 0.82). Aortic dissection decreased the circulating glycine level (P = 0.00168, OR: 0.98, 95 % CI: 0.98, 0.99). Conclusion: Through bidirectional MR analysis, we found that tyrosine level was negatively correlated with other aneurysms and that aortic dissection reduced circulating glycine. Our findings support a possible interaction between circulating amino acid levels and arterial aneurysms and dissection.